Vasodilatory effect of nitroglycerin in Japanese subjects with different aldehyde dehydrogenase 2 (ALDH2) genotypes - Miura, Takeshi; Nishinaka, Toru; Terada, Tomoyuki; Yonezawa, Kazuya (Chemico-biological interactions, 2017)
The functional genetic polymorphism of aldehyde dehydrogenase 2 (ALDH2) influences the enzymatic activities of its wild type (Glu504 encoded by ALDH2*1) and mutant type (Lys504 encoded by ALDH2*2) proteins. The enzymatic activities of mutant-type ALDH2 are limited compared with those of the wild type. ALDH2 has been suggested as a critical factor for nitroglycerin-mediated vasodilation by some human studies and in vitro studies. Currently, there is no research on direct observations of the vasodilatory effect of nitroglycerin sublingual tablets, which is the generally used dosage form. In the present study, the contribution of ALDH2 to the vasodilatory effect of nitroglycerin sublingual tablets was investigated among three genotype groups (ALDH2*1/*1, ALDH2*1/*2, and ALDH2*2/*2) in Japanese. The results by direct assessments of in vivo nitroglycerin-mediated dilation showed no apparent difference in vasodilation among all genotypes of ALDH2. Furthermore, to analyze the effect of other factors (age and flow-mediated dilation), multiple regression analysis and Pearson's correlation coefficient analysis were carried out. These analyses also indicated that the genotypes of ALDH2 were not related to the degree of vasodilation. These results suggest the existence of other predominant pathway(s) for nitroglycerin biotransformation, at least with regard to clinical nitroglycerin (e.g., a sublingual tablet) in Japanese subjects. •Nitroglycerin-mediated vasodilation was compared among different genotypes of ALDH2.•No apparent difference in vasodilation among different genotypes of ALDH2 was found.•ALDH2 is not a key regulator of nitroglycerin-induced vasodilation in Japanese subjects.